2022
DOI: 10.1101/2022.10.19.512889
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cultural determinants of the gap between self-estimated navigation ability and wayfinding performance: evidence from 46 countries

Abstract: Cognitive abilities can vary widely. Some people excel in certain skills, others struggle. However, not all those who describe themselves as gifted are. One possible influence on self-estimates is the surrounding culture. Some cultures may amplify self-assurance and others cultivate humility. Past research has shown that people in different countries can be grouped into a set of consistent cultural clusters with similar values and tendencies, such as attitudes to masculinity or individualism. Here we explored … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…In the UK sample we tested, it is likely many participants would use GPS-based systems to find their way and might rarely find themselves in the situation simulated in the wayfinding task; where a map is studied and must be committed to memory before navigation. When we recently sampled a large population, drawn from many nations and a range of ages, we found a consistent relationship between wayfinding performance in SHQ and self-rated navigation ability (Walkowiak et al, 2022). Thus, the relationship between self-ratings and wayfinding performance is likely moderated by a wide range of factors (e.g., He & Hegarty, 2020; Hegarty et al, 2006; van der Ham & Koutzmpi, 2022; Van der Ham et al, 2021).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In the UK sample we tested, it is likely many participants would use GPS-based systems to find their way and might rarely find themselves in the situation simulated in the wayfinding task; where a map is studied and must be committed to memory before navigation. When we recently sampled a large population, drawn from many nations and a range of ages, we found a consistent relationship between wayfinding performance in SHQ and self-rated navigation ability (Walkowiak et al, 2022). Thus, the relationship between self-ratings and wayfinding performance is likely moderated by a wide range of factors (e.g., He & Hegarty, 2020; Hegarty et al, 2006; van der Ham & Koutzmpi, 2022; Van der Ham et al, 2021).…”
Section: Discussionmentioning
confidence: 85%
“…Our team capitalised on these possibilities by developing a set of tests for navigation ability in the form of the video game app Sea Hero Quest (SHQ) (Spiers et al, 2023). We have employed SHQ to test the navigation ability of 3.9 million people across the world (Coutrot et al, 2018; Walkowiak et al, 2022). SHQ has good test-retest reliability (Coughlan et al, 2020), and has been shown to be predictive of real-world navigational performance (Coutrot et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating objective sleep-based measures and neural recordings in such studies will help identify individuals who may be more likely to benefit from sleep-based therapeutic interventions and effectively target those at greater risk of cognitive decline. Additionally, conducting these studies across countries and cultures will help determine the extent to which associations between sleep and navigation performance may differ across different populations, as has been shown for both self-reported sleep duration 53 and self-reported navigation ability 54 . Such future studies would also benefit from using a broader range of virtual navigation and spatial memory tests, that extend to real-world environments 5,[55][56][57][58][59] .…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…The link between handedness and large-scale navigation is complicated by the fact that cultural differences have a significant impact on both. Differences in nationality and culture are associated with variation in spatial navigation ability (Coutrot et al, 2018;Spiers et al, 2021;Walkowiak et al, 2022;Newcombe et al, 2022). Hand-preference distribution also varies widely between countries, likely due to different cultural pressures (Papadatou-Pastou et al, 2020): left-handers constitute 15-20% of the population in North America but only 0.06-2.8% in China (Kushner, 2013;Raymond & Pontier, 2010;Zverev, 2006).…”
Section: Introductionmentioning
confidence: 99%